Green and resilient hotel operations through mega-event legacies - Sarvinoz Atoevna, Toyirova; Canós-Darós, Lourdes; Osorio-Acosta, Estefanía (Frontiers in Sports and Active Living, 2025)
Mega-events such as the Olympic Games, World Cup, and World Expo aim to leave sustainability legacies, yet the mechanisms through which these goals are realized in hotel operations remain underexplored. This study adopts a multiple case study design, analyzing secondary data including sustainability reports, certification documents, and post-event assessments from five host cities—London, Tokyo, Dubai, Rio de Janeiro, and Doha. The findings reveal that mega-events can serve as catalysts for sustainability upgrades in hotels, including energy-efficient technologies, employee training, and guest-oriented green initiatives. However, not all legacies are uniformly positive: issues such as short-lived initiatives, cost burdens, and limited accountability mechanisms persist. This study contributes to tourism and event management literature by demonstrating how hotels, as essential components of tourism infrastructure, operationalize event-time sustainability commitments into longer-term environmental and social value. It also highlights the interplay of motivations (branding, regulation, guest expectations), constraints (financial and operational), and outcomes (emissions reduction, organizational resilience). While many upgrades offer both financial and reputational benefits, others require trade-offs, confirming that sustainability legacies are complex, context-dependent, and not universally “win-win”.